Metodologia de projeto otimizado de conversores estáticos aplicados a sistemas fotovoltaicos - Beltrame, Fernando (2017)
This work proposes an optimized design methodology for static converters applied to systems where the processed energy is discontinuous and/or variable over time. It will be demonstrated that in these cases, it is not just to design the converter in order to have the maximum efficiency at the rated power of the system, in the worst case or a previously defined point. In most of the time, these converters will operate in several other load processing regions. Thus, the proposed methodology will take into account the behavior of this energy processed by the converter. The maximization of an equation that represents this behavior, together with the minimization of the Boost DC / DC converter volume, working as tracking of the maximum power of a photovoltaic system, will be the criteria to be optimized by this methodology. The search for the ideal solution will be performed through a sweeping of design parameters such as inductor current ripple, switching frequency, output voltage ripple and current density. A database with several magnetic cores, semiconductors and capacitors will be used for different design can be tested. For case study, the methodology will be applied to a photovoltaic system, considering the statistical data of solar irradiation from the meteorological station of São Martinho da Serra / RS.